The Impact of Strategic Planning on Management in Higher Sports Education Institutions - Seymur Aliyev; Yusif Valiyev; Kifayat Huseynova; Taleh Khalilov (International Journal of Computational and Experimental Science and Engineering, 2025)
Strategic planning is essential for the effective management of higher sports education institutions. It serves as a roadmap for decision-making, resource allocation, and institutional growth. By implementing well-structured strategic management frameworks, institutions can enhance their operational efficiency, improve educational outcomes, and foster sustainable development.This paper examines the role of strategic planning in shaping the governance of sports education institutions. It explores how institutions set long-term goals, develop policies, and allocate resources to align with their mission and vision. The study also highlights the challenges faced in implementing strategic plans, such as financial constraints, changing regulatory environments, and technological advancements. By analyzing key strategic management models, this research identifies best practices for integrating strategic planning into the administration of higher sports education. The findings suggest that a well-defined strategic approach not only enhances institutional competitiveness but also contributes to the overall development of sports education by ensuring the efficient use of resources, fostering innovation, and adapting to emerging trends. In conclusion, strategic planning is a critical component in the success of higher sports education institutions. It provides a structured framework for continuous improvement and helps institutions navigate complex challenges. The study emphasizes the need for dynamic and adaptive strategies to ensure sustainable growth and excellence in sports education.